Evolution of Welfare Theories in the Postulates of Economic Schools and Concepts - Iryna Hrynchyshyn (Науковий вісник Мукачівського державного університету. Серія Економіка, 2020)
The relevance of the study lies in the fact that welfare is a fundamental concept that was formed in the origins of economic schools and theories. The purpose of the study is to examine the evolution of welfare theories of economic schools and concepts. The study used the method of logical analysis, critical analysis to examine scientific literature, theoretical aspects of the subject. It is established that the theory of welfare was marked by polarised trends in the prevalence of the market or state; the theory of welfare is based on the imperatives of economic growth (location theories, neoclassical theories, theories of cumulative growth, institutional theories, and new theories of regional development); search for indicators of human development that go “beyond GDP”. It is discovered that the rethinking of approaches to local and regional development at the present stage is associated with the actualisation of endogenous development and the place-based theory. The study also identified that along with the theories of welfare based on the economic concept, international studies spread theories that determine the social status of people from the standpoint of their high standard of living and human development. The conducted research on the evolution of welfare theories indicates the need to develop and implement a national policy that activates local development and provides high-quality public services. The study was determined by many parameters: starting from the type of social structure, the existing socio-economic situation in the country, ending with the development of institutions and the features of the development and use of financial resources